2022
DOI: 10.3389/fpsyt.2022.813969
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Ego- and Altercentric Biases in High-Functioning Autism Spectrum Disorder: Behavioral and Neurophysiological Evidence

Abstract: Self-other distinction is a crucial aspect of social cognition, as it allows us to differentiate our own mental and emotional states from those of others. Research suggests that this ability might be impaired in individuals on the autism spectrum, but convincing evidence of self-other distinction difficulties in the emotional domain is lacking. Here we aimed at evaluating emotional self-other distinction abilities in autistic and non-autistic adults, in two behavioral pilot studies and one fMRI study. By using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 64 publications
2
7
1
Order By: Relevance
“…Importantly, the EEB was not larger than the EAB, which has been described in some prior studies (Silani et al, 2013;von Mohr et al, 2020). However, mixed results have been described in previous studies, too (Bukowski et al, 2020;Hartmann et al, 2022;Silani et al, 2013), which used different sensory modalities and tasks. Here, only the lab study showed a significant three-way interaction of congruency, target, and valence, where follow up results showed an EEB effect for the pleasant condition only, whereas the EAB effect was significant for both valences.…”
Section: Eeb and Eab In The Online Studies And Lab Studysupporting
confidence: 46%
“…Importantly, the EEB was not larger than the EAB, which has been described in some prior studies (Silani et al, 2013;von Mohr et al, 2020). However, mixed results have been described in previous studies, too (Bukowski et al, 2020;Hartmann et al, 2022;Silani et al, 2013), which used different sensory modalities and tasks. Here, only the lab study showed a significant three-way interaction of congruency, target, and valence, where follow up results showed an EEB effect for the pleasant condition only, whereas the EAB effect was significant for both valences.…”
Section: Eeb and Eab In The Online Studies And Lab Studysupporting
confidence: 46%
“…Typically developed individuals responded by the greater recruitment of the ventral mPFC during self‐related information processing relative to the processing of other‐related information, whereas individuals with ASD did not. Along with the decreased recruitment of the ventral mPFC during the processing of self‐relevant information, it has been shown that there is also a decreased recruitment of the dorsal mPFC and the TPJ during other‐relevant information processing (Hartmann et al., 2022; Murdaugh et al., 2014; Padmanabhan et al., 2017). This reflects neurobiological deficits in processes that facilitate social awareness and understanding.…”
Section: Neurodevelopmental Disordersmentioning
confidence: 99%
“…In the egocentric perspective, others are represented in relation to the self, whereas in the allocentric perspective, the mental states of others are represented independent of the self. Recently, Hartmann and colleagues [ 29 ] investigated via behavioral and fMRI studies the emotional self-other distinction in autistic (ASD) people (ASD). ASD is another clinical condition explained as being caused by a ToM deficit, with symptoms like the negative ones seen in individuals with schizophrenia [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…ASD is another clinical condition explained as being caused by a ToM deficit, with symptoms like the negative ones seen in individuals with schizophrenia [ 30 , 31 ]. Although behavioral studies revealed no differences, brain activation studies suggested that two different regions are recruited in autistic individuals when they deal with conflicting emotional mental states that they attribute to themselves or to another person [ 29 ].…”
Section: Introductionmentioning
confidence: 99%